Psychological distress and social support among nurses in outpatient clinics at Hospital Universiti Sains Malaysia (USM) - Ngah, Nurul Hafiezatul Akma Awang Ngah (Universiti Sains Malaysia, 2024)
Psychological distress among nurses is considered as a serious condition due to the increased prevalence in 113 countries from 2009 to 2021. The distress might occur due to various factors depends on their surroundings. The aim of this study was to determine the prevalence of psychological distress and social support among nurses in outpatient clinics at HUSM. A cross-sectional study done by involving 86 participants using face-to-face interview. The questionnaire used in this study was a self-administered questionnaire that consists of three sections which includes sociodemographic data, SRQ-20 to assess the prevalence of psychological distress and MSPSS to assess the level of social support. The data collected was analysed using the SPSS software version 27.0. Descriptive statistic was used to identify the prevalence of psychological distress and to assess the level of social support. Meanwhile, Pearson Correlation Test was used to determine the association between the two variables. The findings revealed that the majority 98.8% had no psychological distress. And as for the level of social support, the results show 77.9% for high level and 22.1% for moderate level of social support, respectively. Lastly, there is no association between prevalence of psychological distress and level of social support (p = 0.060). However, there is similar studies that states there is a correlation between prevalence of psychological distress and level of social support. Thus, more studies need to be conducted in the future to get more precise and accurate findings.